Insomnia among Elderly People in a selected urban Community - Shrestha, Shristika; Roka, Tara (Journal of Nepal Health Research Council, 2023)
Background: Insomnia affects both physical and mental well-being of elderly people, also increasing risks of psychological problems such as depression and decreases quality of life. We assessed the proportion of elderly people with insomnia and associated factors in a selected community. Methods: We carried out a cross sectional study interviewing 110 elderly people residing in Shankarapur-7, Sankhu, Kathmandu using convenient sampling technique. We used a structured questionnaire and included Insomnia Severity Index to identify level of insomnia. We analysed insomnia as clinically significant and non-significant and present the results as proportion and further bivariate analysis. Results: About one third (29.1%) of the elderly had clinically significant insomnia. About half (53%) of the participants suffered from co-morbid disease conditions, mainly hypertension and diabetes mellitus. About 2 in 5 (38%) participants performed regular exercise for more than 15 minutes. Similarly, the proportion of clinically significant insomnia was higher among older age groups (50% among 70+ years & 21% among below 70 years), females 40% (males 19%), widowed 56% (currently married 21%), illiterate 42% (literate 13%). These were found to be significant during bivariate analysis. Conclusions: We found a substantial proportion of participants with clinically significant insomnia. Promoting the physical and mental health of elderly people is important for them to lead a quality life. Health promotion approaches with targeted interventions for elderly are important to cater the need of elderly population and this might help improve the quality of life of the elderly people. Keywords: Community; elderly; insomnia; Kathmandu; Nepal